Signalling by inositides : a practical approach - Shears, Stephen (IRL Press at Oxford University Press, 1997)
"Inositide research has infiltrated numerous branches of biochemistry, physiology, and molecular biology. Consequently, methodological information has been scattered far and wide. This book unites a wide selection of the most fundamental and commonly used techniques. Contributors come from international signal transduction laboratories that have been actively involved in developing and refining these techniques. A unique feature of the book is a catalog of non-commercial sources of synthetic inositide analogues. Because there's an emphasis on broader applications instead of the more esoteric methods, this latest volume in the Practical Approach series is useful as an introduction and a refresher for new and seasoned inositologists, respectively."--Publisher
Keywords: Inositol phosphates.; Inositol.; Phospholipids.; Phospholipases.; Cellular signal transduction.; Inosite.; Signal Transduction; Inositol Phosphates; Inositol; Phospholipids; Phospholipases; Phospholipides.; Transduction du signal cellulaire.; SCIENCE -- Life Sciences -- Biochemistry.; Inosite; Cellular signal transduction; Inositol phosphates; Signalen.